2011
DOI: 10.1148/radiol.10100319
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis in Patients with Chronic Hepatitis C: Noninvasive Diagnosis by Means of Real-time Tissue Elastography—Establishment of the Method for Measurement

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.10100319/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 23 publications
1
110
0
2
Order By: Relevance
“…We analyzed the strain ratio of the ovarian stroma, which we thought to be more objective than the elasticity pattern, because it showed images of relative tissue hardness (18). The strain ratio is a semiquantitative measurement of hardness of the lesion with respect to the adjacent soft tissues, where higher ratios point to harder tissues (9).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the strain ratio of the ovarian stroma, which we thought to be more objective than the elasticity pattern, because it showed images of relative tissue hardness (18). The strain ratio is a semiquantitative measurement of hardness of the lesion with respect to the adjacent soft tissues, where higher ratios point to harder tissues (9).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have evaluated its use in the study of hepatic fibrosis in patients with chronic liver disease (viral in most cases), and the results have shown good concordance with histological data [24,25]. Takahashi et al, for example, found that liver stiffness measured with ARFI correlates with Metavir scores of liver fibrosis.…”
Section: Introductionmentioning
confidence: 95%
“…Because many diseases correlate with changes in the mechanical properties of tissues, this technique has been successfully applied in detecting and assessing various pathologies of thyroid gland, breast, lymph nodes, major salivary gland, prostate, kidney, and liver [1][2][3][11][12][13][14][15][16][17]. However, to our knowledge, no study has been reported previously in the medical literature using real time sonoelastography to assess gallbladder polyps.…”
Section: Discussionmentioning
confidence: 99%
“…B-mode and real-time elastographic images were simultaneously presented as a twopanel image, and the elastogram was displayed in a color scale that ranged from red (greatest strain, softest component), to green (average strain, intermediate component), to blue (no strain, hardest component) [10]. Elastography scans were performed according to a standard protocol as follows: after identification of a gallbladder polyp on a gray scale ultrasound image, real-time elastography was performed using the same probe while applying minimal pressure to the probe, since the gallbladder itself receives pressure from the heartbeat [11]; images were obtained only when optimal compression was in the 5-7-bar range [3]; the scanning protocol was completed after confirming that several stable and reproducible images depicted almost the same color map of the polyp; static and moving images were also recorded for later review; elasticity properties were decided in consensus by two radiologists.…”
Section: Equipment and Scanningmentioning
confidence: 99%